Analysis of the Resistance of Steel Materials in Building Structures Against Fire and the Effectiveness of Fireproofing Systems on Steel Structures in High-Rise Buildings - Valiant, Rizqi; Jody Martin Ginting; Ade Jaya Saputra (Journal of Civil Engineering and Planning (JCEP), 2025)
This study aims to determine the fire resistance of steel materials and analyze the type and thickness of fireproofing systems on the fire resistance of steel structures in high-rise buildings and modules in the oil & gas sector. The main problem to be solved is how this fireproofing system can extend the time of steel resistance to high temperatures before experiencing structural failure and can provide evacuation time. This study uses a quantitative approach with a post-test-only control group experimental design. The research sample consists of steel specimens coated with two types of protective materials, namely intumescent fireproofing and cementitious fireproofing with three different thicknesses (10 mm, 20 mm, and 30 mm). Data collection was carried out through direct testing of resistance time, temperature increase, and structural changes in the steel material. The test results show that steel specimens without fireproofing will experience structural failure in approximately 60 minutes. Meanwhile, steel coated with a 30 mm thick intumescent fireproofing layer can last up to 120 minutes, while a 30 mm thick cementitious fireproofing layer shows the same resistance as intumescent. Quadratic regression analysis and Fourier conduction law show a positive relationship between increasing coating thickness and fire-resistant time. This study concludes that the implementation of appropriate fire-resistance systems can improve the durability of steel in high-rise buildings and oil and gas modules, extend evacuation times, and reduce the risk of structural collapse. These findings significantly contribute to fire safety policy and fire-resistant building design practices.